Exploring the sustainable retirement village concept in the Malaysian context : An initial review / Ruth Lua Ejau ... [et al.] - Ejau, Ruth Lua; Julaihi, Farah Ajlaa; Amat Rais, Syamimi Liyana; Mohamad Bohari, Asmah Alia (Universiti Teknologi MARA Cawangan Sarawak, 2021)
The sustainable retirement village is designed for senior citizens to enhance the quality of the living environment by providing suitable accommodation, services, and facilities which meet residents' social, economic, and environmental needs. The concept of a sustainable retirement village can be adopted in Malaysia as the population aged 65 years and older is expected to increase to 24 per cent in 2050. However, in Malaysia, the provision of the elderly home is still at the introduction phase, and the concept of a retirement village is not clear because there is no technical and legal definition.